Improving Product Photo Understanding for Product Marketing Performance - Robetmi Jumpakita Pinem (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2021)
The continuing social media and trends provide entrepreneurs, including students who want to start their business. A large number of users and ease of access to social media and incentives are a great opportunity for entrepreneurs to do their product marketing online. One of the major issues that are important to note in online marketing is the feasibility of a product photo because a photo of the product is one of the factors that influence consumer purchase decisions. In order to increase their understanding of the product photo in performing online marketing, the Department of Business Administration will be performing training activities to Improving Understanding of the Product Photo for the Product Marketing Performance at the Faculty of Social and Political Science Diponegoro University. Students of Faculty of Social and Political Science Diponegoro University need digital coaching to improve marketing performance.